ADAPTASI STRATEGI MANAJEMEN DALAM PEMBELAJARAN JARAK JAUH: PEMBELAJARAN PADA ERA PASCA PANDEMI - Supriyono, Supriyono (Jurnal Visi Ilmu Pendidikan, 2024)
This research aims to gain deeper insights into the experiences and perceptions of 50 fourth-semester students in the Economics Education program at Universitas PGRI Argopuro Jember (UNIPAR) during the academic year 2022/2023 regarding their learning and adaptation experiences during the COVID-19 pandemic and post-pandemic period. The research method employed is qualitative, utilizing a questionnaire as the primary data collection instrument. The findings of the study indicate that students faced various challenges in navigating remote learning during the pandemic and beyond. They faced technical issues and had trouble staying motivated and focused during online learning. However, as time passed after the pandemic, some students showed better adaptation to this new learning environment. Additionally, the study identifies key adaptation strategies used by students during and after the pandemic, such as improving time management and seeking assistance from lecturers and peers. These insights greatly enhance our understanding of how students manage remote learning challenges in both pandemic and post-pandemic contexts.